Digital Revolution and means of E-Money Circulation: Overview (Trinity Journal of Management, IT & Media (TJMITM), 2017)
technological development. There can be no doubt that this system introduces a new means  of payment, in the form of an electronic purse loaded with  electronic units which can be used to transfer funds and fulfil a  money obligation. However, describing an electronic purse as a In the past several years, many economists have considered the  impact of the digital revolution on the money and banking system,  and by extension the macro-economy. Although many of the  papers on e-money and e-banking have contained useful  insights into these developments, they have also tended to paint  an incomplete and even confusing picture. The application of  information technology to money and banking raises many  interesting questions. But to make further progress in  understanding the economic effects, we need to advance in two  areas. First, we need to settle on a fundamental set of questions  that a theory of electronic money and banking should answer.  Second, we must build frameworks that can address the basic  questions raised by electronic money and banking. On a national level, studies have proven that the more connected  a country's banks; national assets, financial sector and citizens  are to each other and the rest of the world, the more economic  prosperity that country enjoys. This research examines how a widespread use of digital money  would affect monetary policy. Widespread use of digital money  could affect central banks in such areas as monetary policy,  banking supervision of the payment system, and the stability of  the financial system. The increased use of E-money has lead to various studies about  the impact this new form of money could have on central banks'  ability to control the money supply. Many economists believe that  E-money could completely replace currency while others feel  that its impact will be less drastic. E-money is the newest payment instrument. As a part of the new  electronic payment system (possible future substitute of  traditional payment), e-money raises the professional interest  about its implications to further development of banking functions  in the global and networked economy. Statistical evidence  confirms the existence of e-money in the developed countries,  which is understandable because of their high technological level  and knowledge and the ability to absorb useful innovations of any  kind. But, although electronic money has been present in their  markets for more than 20 years, its use is still at a very low level.  The reason could be found in the level of economic and  means of payment is not sufficient in itself, bearing in mind that  means of payment such as bank notes and coin, cashless  payment media like cheques and payment cards, and even debt  securities do not have a uniform status and are not governed by a  uniform set of rules.
Keywords: E – money: E-money; Seignorage Income: The interest saving the government earn by issuing non- interest bearing debt in the form of currency; Credit Card (CC); Debit Card (DC)